Effect of Alcoholic Extracts of Abroma Augusta & Gymnema Sylvestre Leaves in the Modulation of Serum Total Cholesterol Levels of Type 2 Diabetes Mellitus Patients - Venkatesan, H.; Karthi, S. A. (International Journal of Psychosocial Rehabilitation, 2020)
Diabetes is a group of metabolic diseases characterized by hyperglycemia resulting from defects in insulin secretion, insulin action, or both. The most common is type 2 diabetes, usually in adults, which occurs when the body becomes resistant to insulin or doesn't make enough insulin. In the past three decades the prevalence of type 2 diabetes has raised dramatically in countries of all income levels. Defects in insulin action and hyperglycemia could lead to changes in plasma lipoproteins in patients with diabetes. The lipoprotein abnormalities commonly present in Type 2 diabetes, include hypertriglyceridemia increasing Serum Total Cholesterol Levels. These high levels serve as risk factors for the development of Micro-vascular and Macrovascular complications at an early age, with associated premature mortality of Type 2 Diabetes mellitus Patients.Leaves of Abroma augusta belonging to Malvaceae family is traditionally being used to treat Diabetes mellitus in India and Southern Asia. Abromine (betaine), Triterpenoids, Flavonoids and Phenolic compounds in Abroma augusta are found to be Anti-diabetic. Gymnema sylvestre belonging to Asclepiadaceae family found in central and peninsular India is a potent Anti-diabetic plant used in folk medicine. Gymnema sylvestre leaves contain Gymnemic acids that also have Anti-diabetic, activity. The alcoholic extracts of Abroma augusta and Gymnema sylvestre were compared for their Cholesterol Modulation effects by means of a Randomized Control Trial on 30 Type 2 Diabetes mellitus patients which was executed with a Placebo control group for higher significance. Out of this, 13 were found to be Hyperlipidaemic and the rest 17 were not Hyperlipidaemic. Pre & Post Treatment Fasting Serum Total Cholesterol Levels of all the patients were analyzed statistically. By the end of the study the Type 2 Diabetes patients with Hyperlipidaemia treated by Abroma augusta & Gymnema sylvestre has shown a statistically significant modulation of Fasting Serum Total Cholesterol levels with a P Value of 0.0247. Meanwhile Type 2 Diabetes patients without Hyperlipidaemia treated by Abroma augusta & Gymnema sylvestre has shown a statistically insignificant modulation of Fasting Serum Total Cholesterol levels with a P Value of 0.929.